Flexural Behavior of Unbonded Prestressed Concrete Bridge Girders - Chenhao Tang; Gang Zhang; Chaojie Song; Xuyang Li; Yonggang Hou (Advances in Civil Engineering)
This paper presents an experimental and numerical investigation on the flexural behavior of unbonded prestressed concrete (PC) T bridge girders. Three unbonded PC T bridge girders with different prestress degrees spanning 3 m were selected to perform four-point bending tests and then determine the flexural performance. Flexural capacity, crack development and failure mode, load-deflection curves, strain in longitudinal rebars, and stress in prestressing strands of unbonded PC T bridge girders are experimentally analyzed. Subsequently, three-dimensional finite element (FE) models are built and validated by experiments to investigate the effect of different design parameters on flexural behavior of bridge girders. Results generated from experiment and numerical studies show that the flexural destruction behavior in unbonded PC T bridge girders experiences elastic, elastic-plastic, and ductility stages, similar to that of PC T bridge girders. The prestress degree and load location have significant influence on the destruction process in unbonded PC T bridge girders. A lower effective prestress degree can reduce the distribution range in cracks and also increase the width of cracks. Stress in prestressing strands under anchor increases rapidly after concrete presents obvious cracks, and the fracture area within prestressing strands increases with the elevation of prestress degree. The aim of this study is to provide a reference for the design and practical application of unbonded PC T bridge girders.